Volunteers Teaching: Learning Assistance Activities To Eliminate Trauma In Cianjur After The Earthquake Disaster - Halimah, Halimah; Ningsih, Dinni Nur Fajrin; Nuraida, Ida; Hakim, Reza Rahman; Aisah, Aisah (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Carrying out community service is one of the Tridharma of Higher Education which must be carried out by lecturers and students. Joining the Teaching Volunteer Team, lecturers and students of FKIP Suryakancana University carried out Tridharma activities in restoring student learning motivation after the earthquake. It is not an easy thing to restore the motivation of students after the earthquake, this is because some of the survivors and injured victims are traumatized so that their mental and psychological conditions are disturbed. This includes children who are a vulnerable group affected by the earthquake in Cianjur Regency. To improve learning motivation for students can also be done by integrating the learning process by playing and using the media as an attraction for students. This service activity was carried out to describe the implementation of learning activities in three villages affected by the gemba disaster in Cianjur.